흰색 팽이버섯 신품종 ‘백운’ 육성 - 임지훈; 오민지; 김민식; 오연이 (Journal of mushrooms, 2023)
Flammulina velutipesis a popular edible mushroom in South Korea, accounting for approximately 30% of the total mushroom export in the country. Despite its significant position in the domestic mushroom industry, approximately 65% of the cultivated F. velutipes are foreign varieties. To secure variety rights and enhance competitiveness in the export market, there is a need to develop domestic varieties with stable production and excellent shelf life. We focused on breeding a new variety called 'Baekwoon' through mon–mon crossing, using 'Baekseung' and an international collection strain (KMCC02260) as parents. Baekwoon exhibited faster mycelial growth rates at 15 °C and 25 °C and higher mycelial growth across four tested media compared to that of the control variety. Under bottle cultivation, Baekwoon had a mycelial cultivation period that was shorter by approximately 2 days compared to that of the control. The yield of Baekwoon was 228.0±10.9 g, 8.3% more than that of the control. Furthermore, Baekwoon displayed distinct morphological features characterized by a larger pileus and thicker stipe compared to that of the control variety. Genetic tests confirmed that Baekwoon is genetically different from both parental strains and the control variety. It is expected that the newly developed F. velutipes variety, Baekwoon, will be evaluated for its adaptation in different regions and actively promoted in the field, ultimately increasing the market share of domestic varieties.